B-cell activity markers are associated with different disease activity domains in primary Sjögren's syndrome. (28th March 2018) - James, Katherine; Chipeta, Chimwemwe; Parker, Antony; Harding, Stephen; Cockell, Simon J; Gillespie, Colin S; Hallinan, Jennifer; Barone, Francesca; Bowman, Simon J; Ng, Wan-Fai; Fisher, Benjamin A
Abstract: Objectives: B-cell activating factor (BAFF), β-2 microglobulin (β2M) and serum free light chains (FLCs) are elevated in primary SS (pSS) and associated with disease activity. We aimed to investigate their association with the individual disease activity domains of the EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) in a large well-characterized pSS cohort. Methods: Sera from pSS patients enrolled in the UK Primary Sjögren's Syndrome Registry (UKPSSR) ( n = 553) and healthy controls ( n = 286) were analysed for FLC (κ and λ), BAFF and β2 M. Pearson correlation coefficients were calculated for patient clinical characteristics, including salivary flow, Schirmer's test, EULAR Sjögren's Syndrome Patient Reported Index and serum IgG levels. Poisson regression was performed to identify independent predictors of total ESSDAI and ClinESSDAI (validated ESSDAI minus the biological domain) scores and their domains. Results: Levels of BAFF, β2M and FLCs were higher in pSS patients compared to controls. All three biomarkers associated significantly with the ESSDAI and the ClinESSDAI. BAFF associated with the peripheral nervous system domain of the ESSDAI, whereas β2M and FLCs associated with the cutaneous, biological and renal domains. Multivariate analysis showed BAFF, β2M and their interaction to be independent predictors of ESSDAI/ClinESSDAI. FLCs were also shown to associate with the ESSDAI/ClinESSDAI but not independent of serum IgG. Conclusion: All biomarkers were associated with total ESSDAI scores but with differing domain associations. These findings should encourage further investigation of these biomarkers in longitudinal studies and against other disease activity measures.